1977
DOI: 10.3177/jnsv.23.299
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 levels of cerebrospinal fluid in patients with a variety of neurological disorders.

Abstract: SummaryThe vitamin B12 levels of cerebrospinal fluid were assayed microbiologically (Lactobacillus leichmannii method) using samples from 44 patients with various neurological disorders, 4 patients with megalo blastic anemia and 34 controls. Twenty-seven controls that did not receive vitamin B12 showed a mean cerebrospinal fluid vitamin B12 level of 21.5pg/ml (range: 0-60). No decrease in cerebrospinal fluid vitamin B12 level was seen in patients with subacute myelo-optico-neuropathy (SMON). High levels of cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Later, a correlation between CQL and an epidemic of subacute myelo-optic neuropathy (SMON) was noted. SMON is an iatrogenic disease of the nervous system; it can directly cause disabling paralysis, abdominal pains, motor paralysis, lower limbs, impaired vision, sensory disturbances, and even death. , It is very common in Japan, where it was reported that more than 10 000 people were affected by this disease in the 1970s. Additionally, the physiological effect of CQL is caused by rapidly increasing histamine release and cell-mediated immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Later, a correlation between CQL and an epidemic of subacute myelo-optic neuropathy (SMON) was noted. SMON is an iatrogenic disease of the nervous system; it can directly cause disabling paralysis, abdominal pains, motor paralysis, lower limbs, impaired vision, sensory disturbances, and even death. , It is very common in Japan, where it was reported that more than 10 000 people were affected by this disease in the 1970s. Additionally, the physiological effect of CQL is caused by rapidly increasing histamine release and cell-mediated immunity.…”
Section: Introductionmentioning
confidence: 99%